An Interpolation Problem in the Class $R[a,b]$ - Dyukarev, Yu. M.; Choque, Rivero A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider an interpolation problem for matrix functions of the class $R[a,b]$. In the nondegenerate case, we describe all solutions in terms of fractional linear transformations. An explicit formula for the resolvent matrix is obtained.